ANALISIS KELAYAKAN AIR TERJUN MANTOWU SEBAGAI WISATA ALAM DI WILAYAH KPHP UNIT II LASALIMU, SULAWESI TENGGARA - Arniawati, Arniawati; Karim, Jufri; Hadjar, Nurhayati; Nikoyan, Anas; Arafah, Nur; Bana, Sahindomi; Gandri, La; Ahmaliun, Lade; Hafidah Nur (Jurnal Belantara, 2024)
The challenge of the Production Forest Management Unit (KPHP) Unit II Lasalimu as a forest management unit at the site level is the management of forests that can support community welfare and increase state foreign exchange. Mantowu Waterfall is one of the tourist destinations in the KPHP Unit II Lasalimu area which is administratively located in Pasarwajo District, Buton Regency. The development of Mantowu Waterfall as a natural tourism needs to be supported by a feasibility analysis. This study aims to analyze the feasibility of Mantowu Waterfall as a natural tourist attraction. The research was conducted through data collection, observation, interviews, Focus Group Discussion. Data analysis using the Guidelines for Analysis of the Operation Area of Natural Tourism Objects and Attractions (ADOODTW) modified based on natural attractions. The results showed that Mantowu waterfall is worth developing with a value of 67.72%. The greatest value is obtained from the attractiveness indicator owned by the waterfall but not supported by infrastructure and accommodation. In addition, the socio-economic condition of people with low welfare levels is a challenge for the development of Mantowu Waterfall as a natural tourist attraction. Involvement of society as a subject to creating an independent productive society.